Pola Hidup Bersih dan Sehat: Analisis Kesadaran dan Tindakan Preventif Orang Tua Pada Anak Usia Dini - Delis Larasati; Ela Amalia; Yeni Susana; Sindi Misriatun; Ira Anggraeni (Al-Marifah | Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The purpose of this writing is to find out the Clean and Healthy Lifestyle with Awareness Analysis and Preventive Action of Parents in Early Childhood, and provide information to readers so that everyone understands the importance of maintaining Clean and Healthy Living Behavior, both inside and outside the home. The strategy used in this writing is qualitative. Based on the results of data analysis, parents' preventive actions and efforts in healthy living behavior are getting used to washing hands before and after eating with soap in running water, getting used to washing hands and feet after leaving the house, eradicating mosquito larvae, tidying and cleaning the house, and disposing of garbage in its place. The author expects all readers to be able to do and play an active and responsible role in maintaining and preserving personal hygiene and environmental cleanliness, both at home and outside the home, in this article entitled Clean and Healthy Living Habits.